Central Serous Chorioretinopathy Induced by Work Stress: A Case Report - Nursalim, Ade J.; Sumual, Vera (e-CliniC, 2020)
Abstrak: Central serous chorioretinopathy (CSC) adalah terkumpulnya cairan serosa di bawah lapisan epitel pigmen retina yang mengakibatkan terlepasnya retina neurosensorik (detachment). Keadaan ini dapat disebabkan oleh berbagai faktor risiko, termasuk stres psikologik. Jenis kelamin laki-laki merupakan salah satu faktor risiko CSC. Terapi kondisi psikologik merupakan pena-nganan utama CSC yang diinduksi oleh stres kerja. Kami melaporkan seorang laki-laki berusia 27 tahun yang datang ke Poliklinik Mata RSUP Prof. Dr. R. D. Kandou Hospital dengan keluhan kekaburan mata kanan yang mendadak sejak seminggu lalu tanpa didahului oleh nyeri pada mata. Pasien juga mengalami kesulitan dalam membaca teks dan mengenali wajah bila hanya menggunakan mata kanannya. Pasien telah pergi ke optik tetapi tidak mendapatkan ukuran kacamata yang sesuai. Pasien bekerja sebagai tenaga administrasi dan akhir-akhir ini mendapatkan beban kerja berlebihan. Pasien mengakui bahwa ia mengalami kesulitan dalam mengatur aktivitasnya, dan merasakan kelelahan sepanjang hari serta kehilangan minat kerja. Hasil pemeriksaan mata mendapatkan visus 6/15 untuk mata kanan dan visus 6/6 untuk mata kiri, dan metamorphopsia sedangkan hasil pemeriksaan oftalmoskopi memperlihatkan adanya edema dengan lingkaran kekuningan dan berbatas tidak jelas pada mata kanan. Pemeriksaan lanjut dengan OCT menunjukkan adanya cairan subretinal pada mata kanan disertai terlepasnya lapisan epitel pigmen. Saat kontrol setelah 36 hari, visus mata kanan telah membaik 6/6F2 dan peme-riksaan OCT menunjukkan penurunan tebal makula dari 289 Î¼m pada kunjugan pertama men-jadi 190 Î¼m, serta tidak tampak adanya cairan subretinal. Simpulan kasus ini ialah central serous chorioretinopathy yang diinduksi oleh stres kerja, dengan penanganan utama ialah terapi psikologik untuk memperbaiki kualitas hidup.Kata kunci: central serous chorioretinopathy (CSC), stres kerjaÂ Abstract: Central serous chorioretinopathy (CSC) is a condition where serous fluid builds up in the retinal pigment epithelium layer which causes neurosensory retinal detachment. This condition is affected by many risk factors, including psychological stress. Male gender is one of the risk factors for CSC. Treatment to the patient's psychological condition can be the main therapy in handling CSC induced by work stress. We reported a 27-year-old male came to the eye clinic at Prof. dr. R. D. Kandou Hospital complaining of sudden blurred vision in his right eye a week ago without initial pain in the eye. The patient also experienced difficulty in reading text and recognizing peopleâ€™s face using the right eye. The patient went to an optic store but he did not find suitable glasses. The patient works as an administrative employee and is currently getting a heavy workload at his workplace. The patient admitted that he had issues in managing his life in a day. Patients felt tired throughout the day and had no interest in making any activities. The results of the eye examination showed vision 6/15 in the right eye and 6/6 in the left eye, metamorphopsia, edema with a yellowish circle with an unclear border on the right eye using ophthalmoscopy examination, and a subretinal fluid image in the patient's right eye with epithelial detachment pigment acquired through the examination with OCT. After 36 days from the first visit, the right eye vision was improved to 6/6 F2 and OCT examination resulted in a decrease in macula thickness from 289 Î¼m at the first visit to 190 Î¼m, and there was no subretinal fluid. In conclusion, this was a CSC case induced by work stress, and the main treatment was psychological therapy in order to improve the quality of life (QoL).Keywords: central serous chorioretinopathy (CSC), work stress